2016
DOI: 10.1007/s00395-016-0538-5
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid receptor (DOR) signaling and reactive oxygen species (ROS) mediate intermittent hypoxia induced protection of canine myocardium

Abstract: Intermittent, normobaric hypoxia confers robust cardioprotection against ischemia-induced myocardial infarction and lethal ventricular arrhythmias. δ-Opioid receptor (DOR) signaling and reactive oxygen species (ROS) have been implicated in cardioprotective phenomena, but their roles in intermittent hypoxia are unknown. This study examined the contributions of DOR and ROS in mediating intermittent hypoxia-induced cardioprotection. Mongrel dogs completed a 20 day program consisting of 5-8 daily, 5-10 min cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 70 publications
5
32
0
1
Order By: Relevance
“…DOR signaling acts at multiple levels, including the inhibition of hypoxic/ischemic disruption of ionic homeostasis [20,29,47], and the regulation of survival/death signals [48,49]. Estrada et al found that DOR protected canine myocardium from cardiac injury under intermittent hypoxia, which demonstrated the important roles of DOR in cardioprotection against hypoxia [50]. In this study, several miRNAs were identified that respond to DOR activation under normoxic and/or hypoxic conditions and most of them were increased in response to DOR activation at various time points, suggesting that DOR signaling regulates cardiac miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…DOR signaling acts at multiple levels, including the inhibition of hypoxic/ischemic disruption of ionic homeostasis [20,29,47], and the regulation of survival/death signals [48,49]. Estrada et al found that DOR protected canine myocardium from cardiac injury under intermittent hypoxia, which demonstrated the important roles of DOR in cardioprotection against hypoxia [50]. In this study, several miRNAs were identified that respond to DOR activation under normoxic and/or hypoxic conditions and most of them were increased in response to DOR activation at various time points, suggesting that DOR signaling regulates cardiac miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…[171][172][173] Interestingly, administration of antioxidant NAC prior to each IHT session abolished protective effects of IHT on ischemic myocardium in dogs. 174 The pineal hormone melatonin is an antioxidant and a free radical scavenger that is deficient in many AD patients. Melatonin also possesses antiamyloidogenic properties.…”
mentioning
confidence: 99%
“…As DOR roles in this setting are not completely understood; DOR blockade effects were evaluated through monitoring its interference with 20-days of hypoxic exposure protection on dogs before occluding coronary arteries. Naltrindole administration at every exposure session almost completely abolished the beneficial effects of hypoxia pre-conditioning through monitoring the severity of arrhythmias and infarct sizes, which indicates the key roles of endogenous DOR activity in cardiac protective conditioning (21) . In addition to the established DOR protective roles, mu receptors have also been investigated; sedatin, which is a synthetic mixed agonist of delta/mu receptors, was investigated on isolated pulmonary fibroblastic cells, sedatin significantly reduced oxidative stress effects on cellular morphology and DNA synthesis ability (22) .…”
Section: Dor Cardioprotective Effectsmentioning
confidence: 78%